Analysis of the Financial Feasibility of the Roma Larier Terrace Hydroponic Farming Business - Meska Haumahu; Izaac T. Matitaputty; Esther Kembauw (International Journal of Multidisciplinary Sciences and Arts, 2025)
The demand for hydroponic vegetables in Indonesia tends to increase every year. The fulfillment of vegetable needs by the community can be answered by using hydroponic farming techniques nutrient film technique (NFT) system. The limited number of hydroponic farmers has an impact on the supply of vegetables that do not meet market demand. The purpose of this study was to analyze the financial feasibility aspects of the Roma Larier Terrace hydroponic farming business. This research method is a survey with descriptive and analytical methods. The results showed that the Roma Larier terrace farming business had a high level of financial feasibility. The results of the net present value (NPV) analysis of this farming business are known to exceed 0 or >0. The internal rate of return (IRR) with a discount rate of 6% reaches 85% and is feasible. The net benefit cost ratio (Net B/C) is known to be 4.01 with the qualification of being feasible. The payback period (PP) has a level of 1.46, meaning that it is less than 5 years so that the farming business can be continued. The break event point (BEP) shows that the Roma Larier Terrace hydroponic farming business is at the break-even point with two product variants, namely 250 grams and 200 grams. It is known that the minimum sales BEP of 250 grams of lettuce is 22,974 and 200 grams is 32,496, while the minimum BEP of the product is that the 250-gram variant must reach 12.35 kilograms, and the 200-gram variant must reach 141.13 kilograms. The feasibility analysis shows that the Roma Larier Terrace hydroponic farming business is feasible.